Eksitensi Siaran RRI Takengon Ditengah Era Digitalisasi - Viana Safrida Harahap; Subhan AB; Suknah Suknah; Husni Fachri; Fitra jayadi (Institut Nalanda, 2025)
There are two problems in this research, namely the first, how is the existence of RRI Takengon in the digitalization era, the second is what is the background for RRI to make radio streaming. The type of data in this study is qualitative data, namely data that describes, explains, and describes the problems with the problems studied. There are two data sources in this study, namely primary data sources, namely data sources obtained from the leadership and staff of LPP RRI Takengon and also some RRI Takengon listeners by asking directly to informants. And secondary data, namely data taken from literature related to the problem to be researched such as books on existence, radio, and online media as well as documents related to what will be researched. The process of analyzing begins with examining all data from various sources, namely from interviews, observations, documents, and so on. While the data collection technique used in this study was field research (Field Research). From the results of this research, RRI continues to strive to present interesting broadcast content not only via terrestrial but also online